PENINGKATAN HASIL BELAJAR IPA SISWA KELAS X TKR 1 SMK N 7 SEMARANG MELALUI JOYFUL LEARNING MENGGUNAKAN GAME GUESS MY WORD - Fibonacci, Anita (Jurnal Penelitian Pendidikan, 2012)
Learning achievements of X TKR1 SMK Negeri Semarang 7 is low, especially on science lesson with an average value of the school year repetition scieence lesson 2010/2011 is 60 (before remidial) with the percentage of students who graduated only 44% percent when passing grade of science lesson is 75. This is certainly a concern to researchers as a science teacher because SMK Negeri 7 Semarang having a good reputation well known in Central Java. This is because the characteristics of a class X TKR1 like to play, and the attitude of solidarity of the group must be upheld, even for things that are less good. It certainly is disturbing the learning process. In an effort to overcome these problems a teacher as a researcher, trying to apply the methods of the game in groups, with the hope that the game will make learning a fun atmosphere, as claimed by Taufan Surana (2008:1) that a pleasant atmosphere is a necessary prerequisite to children love to learn. The purpose of this study were (a) To improve science learning outcomes in class X TKR 1 (b) To determine a significant improvement in student learning outcomes. Research subject is X TKR1 SMK N 7 Semarang, which is located in Lima Jl.Simpang Semarang. Research will be conducted in May to June. The analysis performed is descriptive analysis, the credibility test using the method of triangulation of data sources. The results of application of joyful learning model using games guess my word is as follows: (a) a large increase in the average classical is 10.4 (Classical 83.4 average at cycle 1 to 93.9), (b) a large increase in the number of students who qualify for passing gradeis 20% from 77% in cycle 1 to 97% in cycle 2. Teachers are expected to be able to apply the learning model â€œJoyful learningâ€ in schools so that learning becomes more enjoyable. The school should be supported by improving facilities and pre facilities, in order to create a fun learning atmosphere for students (Joyful Learning).